Pengembangan Mekanisme Otentikasi Dan Otorisasi Manajemen Config Pada Kasus Shared Web Hosting Berbasis Linux Container - Saifuddin, Saifuddin; Ijtihadie, Royyana Muslim; Pratomo, Baskoro Adi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2016)
A large part of the service providers website using an operating system Linux, when one of the websites in the Shared web can be taken over, most likely other websites will also be mastered by reading config connecting to the database, the mechanism used to read a config file with the command in linux by default is available, using the command ln -s also known by the term symlink who can read the directory where the web, although different config directory.The results show config on web applications that are in the directory in a single server can be read using these methods but can not be decoded to read user, password, and dbname, because it has given authorization can be decoded only from the directory already listed. on testing performance for latency, memory, and CPU system be followed, to get good results the previous system. The test results using the cache, the response time generated when accessed simultaneously by 20 click per user amounted to 941.4 ms for the old system and amounted to 786.6 ms.